Incidence of Peripheral Neuropathy in Major Beta-Thalassemia Patients at Hasan Sadikin General Hospital, Bandung, Indonesia - Fanny Adhy Putri; Uni Gamayani; Nushrotul Lailiyya; Ramdan Panigoro (PT. Kalbe Farma Tbk., 2019)
Bakground. Beta major thalassemia is the most common inherited blood disorder worldwide. It can lead to various neurological complications such as peripheral neuropathy. Toronto Clinical Neuropathy Score (TCNS) is helpful for peripheral neuropathy screening especially in diabetes mellitus. Objective. To investigate the prevalence of peripheral neuropathy in beta major thalassemia patient using Toronto Clinical Neuropathy Score (TCNS). Method. A descriptive study on beta major thalassemia patients aged more than 14 years who regularly underwent blood transfusions in Hasan Sadikin General Hospital Bandung, from July to August 2017. Normal TCNS values was < 4, mild neuropathy 5-7, moderate neuropathy 8-10 and severe neuropathy > 10. Results. Sixty subjects met the inclusion criteria, 48,3% were male with the mean (SD) age of 20,7 ± 7,6 years. Mean hemoglobin value was 6,7 ± 0,9 g/dL and median (IQR) blood ferritin serum was 2873 (1900-3859) μg/L. Thirty-two subjects had neuropathy; 19 (31,7%) with mild neuropathy and 13 (21,6%) with moderate neuropathy.Conclusion. The incidence of peripheral neuropathy in patients with thalassemia according to TCNS score is fairly high.Latar Belakang. Talasemia beta mayor adalah kelainan darah bawaan paling umum di dunia dan dapat menyebabkan berbagai komplikasi, salah satunya neuropati perifer. Toronto Clinical Neuropathy Score (TCNS) dapat digunakan untuk penilaian neuropati perifer yang disebabkan oleh berbagai penyakit sistemik. Objektif. Menyelidiki prevalensi neuropati perifer pada pasien talasemia beta mayor menggunakan Toronto Clinical Neuropathy Score (TCNS). Metode. Penelitian ini studi deskriptif skrining menggunakan TCNS pada pasien thalassaemia beta mayor berusia lebih dari 14 tahun yang secara teratur menjalani transfusi darah di Rumah Sakit Umum Hasan Sadikin Bandung, dari Juli hingga Agustus 2017. Nilai TCNS normal adalah <4, neuropati ringan 5-7, neuropati sedang 8-10 dan neuropati berat> 10. Hasil. Sebanyak 60 subjek memenuhi kriteria inklusi, 48,3% laki-laki dengan usia rata-rata (SD) 20,7 ± 7,6 tahun. Nilai hemoglobin rata-rata 6,7 ± 0,9 g / dL dan serum ferritin darah median (IQR) adalah 2873 (1900-3859) μg / L. Tiga puluh dua subjek memiliki neuropati; 19 (31,7%) neuropati ringan dan 13 (21,6%) neuropati sedang. Simpulan. Insiden neuropati perifer pada pasien dengan talasemia menurut skor TCNS cukup tinggi.